Causes of interpersonal conflict and biparti institution contribution in handling conflict towards tourism industry - Sudharma , Kadek Januarsa Adi; Haes, Putri Ekaresty (International research journal of management, IT and social sciences, 2020)
This article contains the results of interpersonal interactions that occur in the tourism industry. This research is a qualitative study using three data collection techniques, namely observation, interviews, and documentation. The following data retrieval results produce the final results about the causes of interpersonal conflict in the tourism industry, namely (1) differences in the meaning of information to cause discrepancies in the work done, (2) the influence of priorities from tourists. This personal characteristic is caused by the self-concept formed in a person, (3) Unresolved old conflicts so that a compilation of new interpersonal conflicts occurs, old conflicts also contribute. (4) Interpersonal conflict also arises because the leadership style that is applied so that it causes discomfort in work which in the end the work productivity does not decrease.